Geographical and institutional distances in venture capital deals: How syndication and experience drive internationalization patterns - Tereza Tykvová; Andrea Schertler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
Drawing on a novel dataset of worldwide venture capital deals, we investigate how venture capitalists (VCs) overcome the complexity of investing in geographically and institutionally distant regions. Our results indicate that syndicating with local VCs is a common way for foreign VCs to gain deal access, overcome the complexity of investing in distant regions and offset their lack of within-country experience. The foreign VC's distance from the portfolio company ceases to be a serious investment obstacle when he can rely on a highly experienced local VC. Our results further suggest that inexperienced VCs, i.e. those VCs with a large need for syndication, increase their chances to invest across borders when they invest in small deals jointly with local inexperienced partners.
urn:nbn:de:bsz:180-madoc-31675
Keywords: F21; G24; 330; Multiple Regression Analysis; Syndicates; Venture Capital; Internationalization; Distance; Experience